1989
DOI: 10.1130/spe238-p75
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sauropod dinosaurs have a temporally disjunct distribution in the North AmericanWestern Interior during Cretaceous time, here referred to as the sauropod hiatus. Sauropod body and ichnofossils are present in inland basinal and coastal deposits of Aptian-Albian age in Wyoming, Texas, Oklahoma, and Arkansas. Body fossils of sauropods (the titanosaurid Alamosaurus) occur in inland basinal deposits of Maastrichtian age in Texas, New Mexico, Utah, and Wyoming. No sauropods of Cenomanian-Campanian age are known from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 4 publications
1
17
0
2
Order By: Relevance
“…Of note is that the contemporaneous OTU comprising a somphospondylan from the Cloverly Formation (‘Cloverly titanosauriform’) is recovered as the sister taxon to Sauroposeidon in our EIW9 analysis (figure 5 c ), which would support the referral of this material to that taxon by D'Emic & Foreman [102]. Stratigraphically younger sauropods are unknown from North America until the Maastrichtian, with the appearance of Alamosaurus sanjuanensis ([65,103]; though see Ryan & Evans [104] for a possible Santonian sauropod occurrence from Canada), although whether this ‘sauropod hiatus’ reflects an extinction followed by ‘re-invasion’, a sampling bias or some combination of both, remains uncertain [9,105].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note is that the contemporaneous OTU comprising a somphospondylan from the Cloverly Formation (‘Cloverly titanosauriform’) is recovered as the sister taxon to Sauroposeidon in our EIW9 analysis (figure 5 c ), which would support the referral of this material to that taxon by D'Emic & Foreman [102]. Stratigraphically younger sauropods are unknown from North America until the Maastrichtian, with the appearance of Alamosaurus sanjuanensis ([65,103]; though see Ryan & Evans [104] for a possible Santonian sauropod occurrence from Canada), although whether this ‘sauropod hiatus’ reflects an extinction followed by ‘re-invasion’, a sampling bias or some combination of both, remains uncertain [9,105].…”
Section: Discussionmentioning
confidence: 99%
“…Alamosaurus is known from the Maastrichtian of the USA [14,64], and is currently the only recognized titanosaur from North America [65,121]. Its biogeographic origin has long been the subject of debate [9,74,103,105,122], with alternative phylogenetic hypotheses supporting dispersal from either: (i) South America, based on a sister taxon relationship with latest Cretaceous taxa such as Baurutitan britoi or Saltasaurus loricatus (e.g. [1,38,40]); or (ii) East Asia, based on a sister taxon relationship with Opisthocoelicaudia skarzynskii (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fauna also includes 33 (46%) stratigraphic range extensions for North American taxa and 28 (39%) on a global scale. Most notable among last North American occurrences is that of Sauropoda, the large, perhaps high-browsing, herbivores that dominated faunas of the Late Jurassic (6) and reappeared briefly in the latest Cretaceous through immigration (19). The vertebrate fauna of the uppermost Cedar Mountain Formation greatly resembles later Cretaceous assemblages, sharing 80% of taxa (at lowest identifiable level); by contrast, only 60% of Cedar Mountain taxa appear in earlier faunas.…”
Section: Faunal Comparisons and Dynamicsmentioning
confidence: 99%
“…Similarly to the ‘sauropod hiatus’ hypothesis proposed by Lucas and Hunt 51 to account for the absence of sauropod fossils for the largest part of the mid to Late Cretaceous interval in North America, Le Loeuff  8 and Le Loeuff and Buffetaut 15 suggested that the fossil record supports the absence of sauropods from the Cenomanian to late Campanian continental vertebrate record of Europe. This assertion was based on the fact that until the end of the 1990’s not even a single bone or footprint, certainly referable to this group, was known from the, admittedly few, European vertebrate localities representing this time period.…”
Section: Discussionmentioning
confidence: 70%